Second language acquisition opportunities during digital game interactions / Kaarthiyainy Supramaniam and Wan Shahirah - Supramaniam, Kaarthiyainy; Shahirah, Wan (Universiti Teknologi MARA, 2022)
Digital Game Based Learning has been studied for its impact on learning in a fun way in the language classroom. Second language learners are said to benefit from the systemic environment of the game that even low proficient speakers are prompted to engage in the target language in a less stressful way. However much past research has adopted a survey stance rather than analysing the interactive patterns emerging from the utterances in real time in understanding second language acquisitions among L2 learners. Therefore, this research focused on two groups (n=8) of secondary school L2 students as they played two rounds of the Werewolf game each to identify the aspects of language that emerged. Findings revealed that their interactions featured negation, lexical borrowing, guessing, repetitions, persuasion and peer-tutoring, of which negation and negotiation were most prevalent. Interestingly, there were also elements of L2 culture. Implications of this study relate directly to the use of digital games for promoting the use of English in a non threatening environment for L2 learners and in furthering current understanding of aspects of second language acquisition among L2 learners.